LEGAL REGULATION OF ASSIGNMENT OF CLASS RANKS OF MUNICIPAL EMPLOYEES - Lubennikova S. A. (Scientific Journal of Pedagogy and Economics, 2019)
This study is devoted to the study of legal regulation of municipal service by the subjects of the Russian Federation, such issues as the process of municipal service work and the implementation of the status of municipal employees. The practical significance is due to the conclusions and recommendations that can find practical application in the law-making and law-enforcement activities of public authorities of the Russian Federation, as well as local authorities. The proposed approaches to the problems of forming a strategy for the development of municipal service in the conditions of improving the legislation of the subjects of the Russian Federation on municipal service have scientific novelty. The article analyzes the legal regulation of the assignment of class ranks of municipal employees at the federal and regional level. The main stages of legal regulation of assignment of class ranks of municipal employees, as well as tendencies of legal regulation are revealed, the reasons of change of the legislation of subjects of the Russian Federation are defined. The author comes to the conclusion that the legal regulation of the order of assignment of class ranks in the subjects of the Russian Federation was not the same. Some entities have not adopted any regulatory legal acts in this area. However, considering the needs of the practice, now there is a change of previously adopted regulations. Regions that have not previously regulated this sphere are now adopting regulatory legal acts. The author has formulated proposals to improve the legal regulation of the assignment of class ranks by legislators of the Russian Federation.